The Implementation of Character Education through the Habituation of Religious Practices - Wakib Kurniawan; Untung Sih Nugroho; Ari Arkanudin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to describe the implementation of character education through the habit of worship in Phase C students in grade 5 Andalusia at SD IT Cahaya Madani Pringsewu. Character education is an important part of the education process, especially at the elementary school level (SD), because this period is the initial phase of the formation of a child's personality. The habit of worship is seen as an effective means of instilling character values ​​such as discipline, responsibility, and religiosity. This study uses a qualitative descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the habit of worship at SD IT Cahaya Madani Pringsewu includes routine activities such as dhuha prayer, morning prayer, recitation of the Qur'an, congregational prayer and sharing activities. These activities are able to shape students' character in terms of discipline, obedience, social concern, and responsibility. Supporting factors for the implementation of this habit are full support from teachers and parents, as well as a religious school environment. The inhibiting factors are the lack of consistency of students at home and the level of student understanding which is still diverse. This study concludes that the habit of worship is an effective strategy in forming students' character from an early age.